Arab TV-Audiences (Peter Lang International Academic Publishers, 2015)
Today the relations between Arab audiences and Arab media are characterised by pluralism and fragmentation. More than a thousand Arab satellite TV channels alongside other new media platforms are offering all kinds of programming. Religion has also found a vital place as a topic in mainstream media or in one of the approximately 135 religious satellite channels that broadcast guidance and entertainment with an Islamic frame of reference. How do Arab audiences make use of mediated religion in negotiations of identity and belonging? The empirical based case studies in this interdisciplinary volume explore audience-media relations with a focus on religious identity in different countries such as Egypt, Tunisia, Algeria, Morocco, Great Britain, Germany, Denmark, and the United States.